The Influence of the Audit Committee and Company Age on the Financial Report Quality of Energy Sector Companies Listed on the Indonesia Stock Exchange - Hintalo, Indrawati; Junus, Onong; Masiaga, Novaliastuti; Ishak, Olfin (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study aimed to analyze the effect of the audit committee and company age on the quality of financial statements in energy sector companies listed on the Indonesia Stock Exchange (IDX). The research sample consisted of 15 companies selected using purposive sampling method based on certain criteria, such as being listed on the IDX main board, having annual financial reports during the 2017-2022 period, and reporting positive profits. The method used in this research is a quantitative approach with multiple linear regression analysis used to test the hypothesis. The results showed that the audit committee had no significant effect on the quality of financial statements, while the age of the company had a negative effect. This finding indicates that the longer the company operates, the possibility of declining financial statement quality, which can be caused by factors such as suboptimal accounting practices or a decrease in the effectiveness of corporate governance. Therefore, stricter oversight is needed to ensure transparency and accountability of financial statements in the energy sector.